Innovation for Education and Research Management at Universidad de la Costa in the pandemic era - Celene B Milanes; Claudia Palacio Salgado; James Frasser Camargo (Journal of Sustainability Perspectives, 2022)
Universidad de la Costa (UNICOSTA) is an institution in the Colombian Caribbean whose main topic of institutional research is sustainable development. UNICOSTA has participated for just one year in the UI Green Metric World University Ranking. In the year 2020, UNICOSTA was ranked 44th at the country level. The aim of this paper is to present the most relevant activities carried out in Universidad de la Costa (UNICOSTA) in the pandemic era by COVID-19, specifically those related to the indicator of Innovation for Education and Research Management. This paper describes in a quantitative way all main research, courses, webinars, and collaboration networks that have been carried out at UNICOSTA from March 2020 to the present. The conclusions show that during the COVID-19 pandemic, the university has strengthened its national and international academic networks ties with several universities, showing as a result an increase in both collaboration and scientific production.Keyword: academic collaboration networks; COVID-19; indicators; sustainable development